Neuropathological Insights into Unexpected Cognitive Decline in Epilepsy. Issue 3 (5th December 2022) - Reimers, Annika; Helmstaedter, Christoph; Elger, Christian E.; Pitsch, Julika; Hamed, Motaz; Becker, Albert J.; Witt, Juri‐Alexander
Abstract : Objective: Some patients unexpectedly display an unfavorable cognitive course after epilepsy surgery subsequent to any direct cognitive sequelae of the surgical treatment. Therefore, we conducted in‐depth neuropathological examinations of resective specimens from corresponding patients to provide insights as to the underlying disease processes. Methods: In this study, cases with significant cognitive deterioration following a previous postoperative assessment were extracted from the neuropsychological database of a longstanding epilepsy surgical program. An extensive reanalysis of available specimens was performed using current, state‐of‐the‐art neuropathological examinations. Patients without cognitive deterioration but matched in regard to basic pathologies served as controls. Results: Among the 355 operated patients who had undergone more than one postoperative neuropsychological examination, 30 (8%) showed significant cognitive decline in the period after surgery. Of the 24 patients with available specimens, 71% displayed further neuropathological changes in addition to the typical spectrum (ie, hippocampal sclerosis, focal cortical dysplasias, vascular lesions, and low‐grade tumors), indicating (1) a secondary, putatively epilepsy‐independent neurodegenerative disease process; (2) limbic inflammation; or (3) the enigmatic pathology pattern of "hippocampal gliosis" without segmental neurodegeneration. In the controls, the matched individual principal epilepsy‐associated pathologies were not found in combination with the secondary pathology patterns of the study group. Interpretation: Our findings indicate that patients who unexpectedly displayed unfavorable cognitive development beyond any direct surgical effects show rare and very particular pathogenetic causes or parallel, presumably independent, neurodegenerative alterations. A multicenter collection of such cases would be appreciated to discern presurgical biomarkers that help with surgical decision‐making. ANN NEUROL 2023;93:536–550